Effect of Agroecological Conditions on Biologically Active Compounds and Metabolome in Carrot - Martin Koudela (Cells, 2021)
Carrot serves as a source of health-beneficial phytochemicals for human diet whose content is affected by agroecological conditions. The effect of conventional, integrated and organic farming on ascorbic acid (AA) and α,β-carotene levels of new carrot cultivars Cortina F1 and Afalon F1 was investigated and their metabolomic profiles were measured by direct analysis in real time ion source coupled with a high-resolution mass spectrometer (DART-HRMS). Cortina and Afalon exhibited high levels of AA and total carotenes under all agroecological conditions tested that fluctuated in broad ranges of 215–539 and 173–456 mg AA.kg–1 dry biomass and 1069–2165 and 1683–2165 mg carotene.kg–1 dry biomass, respectively. The ratio of β- to α-carotene in both cultivars was about 1.3. The most important variable for the PCA and the partial least squares discriminant analysis (PLS-DA) models for ethyl acetate extracts measured in positive and negative ionization mode was 6-methoxymellein (6-MM). Total carotene content and 6-MM levels were higher in the organic carrot compared to the conventional one and were correlated with a higher level of spontaneous infection. Other important compounds identified were sitosterol, hexose and various organic acids including antioxidant ferulic and coumaric acids. The findings allow comparison of metabolomic profiles and the AA and carotene contents of both cultivars with those of other commercially used carrots.